ACADEMIC ACHIEVEMENT OF ADOLESCENTS IN RELATION TO THEIR ACHIEVEMENT MOTIVATION - Gurung, Kabita; Ghosh, Shilpi (International Journal of Psychosocial Rehabilitation, 2021)
Achievement motivation has been referred to as the need for achievement, a desire to perform well, that controls a person’s behaviour relevant to achievement and learning. It encourages and directs students’ behaviour toward putting in more effort and therefore is found to be an important determinant of academic achievement. There are many factors that affect the achievement motivation of an individual; among those factors, gender and school management are shown to have a great influence on the achievement motivation of the students by some studies. Adolescence is the period of vulnerability when they are at risk of developing psychological ill-being and feel increased pressure to succeed academically, and therefore, more attention needs to be paid to it to provide them all the required help at this crucial juncture. Hence the purpose of this study is to investigate the influence of achievement motivation on academic achievement of adolescent students and also to find out whether gender and school management variables have any effect on students' achievement motivation. It is a correlational study and focused on 100 students of East Sikkim. The Achievement Motivation Scale (n-Ach), developed by Prof. Pratibha Deo and Dr. Asha Mohan (2011), is used as a tool. The study revealed the influence of achievement motivation on academic achievement of the students; also, gender and school management are found to have positive effects on achievement motivation of the students.